Stories of Learning: A Case Study of Norwegian Plumbers and Apprentices in TVET at the Construction Site and in a Training Agency - Marit Lensjø (International Journal for Research in Vocational Education and Training, 2020)
Context: Through a dual model, based on 2 years of education in upper secondary school followed by two and a half year of apprenticeship training, Norwegian plumbing education has become an integrated part of the Technical Vocational Education and Training (TVET). Competence and skills are described in national plumbing curriculum. However, there is little information on how learning and training, interaction and relations between craftsmen and apprentices take place and develops at the workplace. The objective of this article is to identify significant learning processes by studying apprentices in a training agency and in communities of plumbers at the building site.